Heuristics for evaluating university library websites: A scoping review from 2012 to 2022 - Valenzuela, Cristian (2025)
In this article, a detailed review of the research that works on usability heuristics to examine the web spaces of university libraries is proposed. The objective is to detect the usability heuristics necessary to evaluate the websites of university libraries, according to scientific literature, between 2012 and 2022. The research was developed using the systematic review methodology, specifically the scoping review modality, applied to six bibliographic databases. Among the results, it is established that there are three categories of heuristics: matching, non-matching and those that have been expressly designed for university libraries. It is concluded that the development of heuristics for university libraries is incipient and that the analysis of a space as complex as this requires a layered heuristic evaluation and the application of different evaluation instruments depending on the purpose of the service and the content of the website.